Correction: In-hospital mortality from severe COVID-19 in a tertiary care center in Mexico City; causes of death, risk factors and the impact of hospital saturation. - Antonio Olivas-Martínez; José Luis Cárdenas-Fragoso; José Víctor Jiménez; Oscar Arturo Lozano-Cruz; Edgar Ortiz-Brizuela; Víctor Hugo Tovar-Méndez; Carla Medrano-Borromeo; Alejandra Martínez-Valenzuela; Carla Marina Román-Montes; Bernardo Martínez-Guerra; María Fernanda González-Lara; Thierry Hernandez-Gilsoul; et al. (PLoS ONE, 2022)
[This corrects the article DOI: 10.1371/journal.pone.0245772.].